Defining Videogame Atmospheres: Böhme applied to Gone Home and What Remains of Edith Finch - Sánchez Trigo, Clara (Analecta Malacitana. Revista de la sección de Filología de la Facultad de Filosofía y Letras, 2025)
Atmosphere is an underdefined term in videogame studies. This paper reviews Gernot Böhme’s aesthetic theory of atmospheres and adapts it to the analysis of video-games to make of atmospheres an analytical category. From this perspective, I analyse two videogames Gone Home and What Remains of Edith Finch to identify what elements are contributing to their affective atmosphere and suggest how they interact with each other. Drawing from Brian Massumi’s reflections on affective resonance, I ponder as well on the interrelation between the games’ atmospheres, their storyline and their mechanics.